DEVELOPMENT OF RESOURCE-SAVING TECHNOLOGICAL SCHEME OF WASTEWATER TREATMENT ENGINEERING ENTERPRISES - Elvira Pavlovna Doskina; Anastasia Vladimirovna Moskvicheva; Darya Olegovna Ignatkina; Pavel Alekseevich Sidyakin (Современная наука и инновации)
Proved the feasibility of disposal of chromium ions (VI) "ballast" coolant components, is investigated and the optimal conditions of reduction reaction of chromium (VI) ions to chromium (III).